The Classical Poet (Kamil Imamy) between Tradition and Creativity - Jabbar Ahmed Hussein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research is entitled (The Classical Poet (Kamil Imamy) between Tradition and Creativity). One of the most notable components of classic poetry is imitation. The value of any poet is estimated through their poetic inventions that also denotes their aesthetic style. Awat, in most of his poems, wrote on basis of the classic artistic and aesthetic conventions. However, he never imitated those conventions blindly; instead, he pursued his creative style. The purpose of this study is to elaborate upon the personal style of the poet, as well; it grapples with the artistic experience of the poet’s life. The study is composed of two aspects and the results, as follows: The first aspect stresses upon the influence that other poets of his age and earlier have remarked on him. Then, his influence on the upcoming poets who came after him is discussed. In the second aspect of the present study, some elements of artistic style in his poems are figured out. Finally, the results of the study are presented briefly in some points.